Assessment of maize stem borer damage on hybrid maize varieties in Chitwan, Nepal - Achhami, Buddhi Bahadur; BK, Santa Bahadur; Bhandari, Ghana Shyam (Journal of Maize Research and Development, 2015)
Maize is the second most important cereal crop in Nepal. However, national figure of grain production still remains below than the world's average grain production per unit area. Thus, this experiment was designed to determine the suitable time of maize planting, and to assess the peak period of one of the major insects, maize stem borer, in Chitwan condition. The results showed that plant damage percentage as per the maize planting month varies significantly, and the average plant damage percentage by stem borer was up to 18.11%. Length of the feeding tunnel in maize stem was significantly higher in January than July. In case of exit holes made by borer counted more than four holes per plant that were planted in the month of January. All in all, except the tunnel length measurement per plant, we observed similar pattern in other borer damage parameters such as exit whole counts and plant damage percentage within the tested varieties. Stem borer damage was not significantly affect on grain yield. Journal of Maize Research and Development (2015) 1(1):53-63 DOI: http://dx.doi.org/10.5281/zenodo.34293